PEMANFAATAN TEKNOLOGI INFORMASI DALAM UPAYA PENINGKATAN PENGETAHUAN MANAJEMEN BISNIS SYARIAH PADA SANTRI MADRASAH TSANAWIYAH DI DESA GUNUNG MENYAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Hinka Lutfiah; Rully Trihantana; Ermi suryani (SAHID EMPOWERMENT JOURNAL, 2021)
Abstract This community service aims for students who are required to do distance learning so as to make learning less than optimal and by using the use of information technology the students of MTS Sahid class 7, totaling 29 students, utilize information technology with online learning. Likewise, teachers must have expertise in managing this information technology to facilitate the distance learning process due to the COVID-19 situation. Making learning so diverse and innovative and making students have or hone their expertise in the field of technology. Keywords: Utilization of Technology, Covid 19, Religious Knowledge